2000
DOI: 10.1016/s0005-2736(99)00192-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grafted polyethylene glycol (PEG) on the size, encapsulation efficiency and permeability of vesicles

Abstract: Liposomes have been prepared by the vesicle extrusion method (VETs) from mixtures of dipalmitoylphosphatidylcholine (DPPC), phosphatidylinositol (PI) and dipalmitoylphosphatidylethanolamine with covalently linked poly(ethylene glycol) molecular mass 5000 and 2000 (DPPE-PEG 5000 and DPPE-PEG 2000) covering a range of 0-7.5 mole%. The encapsulation of D-glucose has been studied and found to be markedly dependent on the mole% DPPE-PEG. The permeability of the liposomes to D-glucose has been measured both as a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 25 publications
4
100
2
1
Order By: Relevance
“…In summary, these results imply that film-rehydration of POPC and PB-PEO block copolymers blends yields nanometer-sized hybrid vesicles over the entire range of compositions studied. The results are significantly different from those obtained in a previous study of micrometer-sized hybrid GUVs formed from POPC and PB-PEO, even though this comprised a higher molecular weight polymer, i.e., PB 46 -PEO 30 (M W for PB and PEO blocks: 2500 and 1300, respectively), and a different preparation method [15]. In the respective study, hybrid GUVs formation was inefficient at high lipid composition (>65 mol %), while at intermediate lipid compositions (35-65 mol %) GUVs were not formed at all.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…In summary, these results imply that film-rehydration of POPC and PB-PEO block copolymers blends yields nanometer-sized hybrid vesicles over the entire range of compositions studied. The results are significantly different from those obtained in a previous study of micrometer-sized hybrid GUVs formed from POPC and PB-PEO, even though this comprised a higher molecular weight polymer, i.e., PB 46 -PEO 30 (M W for PB and PEO blocks: 2500 and 1300, respectively), and a different preparation method [15]. In the respective study, hybrid GUVs formation was inefficient at high lipid composition (>65 mol %), while at intermediate lipid compositions (35-65 mol %) GUVs were not formed at all.…”
Section: Resultscontrasting
confidence: 99%
“…Simulation and experimental studies have suggested block copolymers with molecular weights below 3 kDa or membrane thicknesses below 7 nm adopt more stretched and ordered membrane configuration (compared to more flexible entangled configuration of long block copolymers), which is consistent with the strongly segregated state of lipids [26,27], making mixing energetically more favorable. To re-confirm this effect, we also performed flow cytometry on nanoscale vesicles prepared from mixtures of POPC and the longer polymer, PB 46 -PEO 30 (M W = 3800). The dot plots results shows the fraction of hybrids to measure 17%-36%, suggesting that the mixing of this copolymer with lipids is indeed less efficient ( Figure S1 and Table S1).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations